On the electrochemistry of an anode stack for all-solid-state 3D-integrated batteries - Baggetto, L.; Oudenhoven, J.F.M.; van Dongen, T.; Klootwijk, J.H.; Mulder, M.; Niessen, R.A.H.; de Croon, M.H.J.M.; Notten, P.H.L. (Journal of power sources, 2009)
This paper will report on the electrochemical and material characterization of a potential planar anode stack for all-solid-state 3D-integrated batteries. The first element of the stack is the silicon substrate. On top of silicon, a Li diffusion barrier layer material is deposited in order to effectively shield the substrate from the battery stack. Several materials are investigated with conventional electrochemical techniques. The best candidates, sputtered and atomic layer deposited (ALD) TiN, are studied in more detail with ex situ X-ray diffraction (XRD) and the reaction mechanism of these materials with Li is discussed. The third element of the stack is the active anode material. Thin films of poly-Si are studied towards their thermodynamic and kinetic properties. Moreover, the growth of SEI layers on top of poly-Si anodes cycled in two liquid electrolytes has been investigated by means of ex situ SEM. Strikingly, when poly-Si is covered with a solid-state electrolyte, prolonged lifetime is found, enabling future 3D-integrated all-solid-state batteries.